Osteoarthritis, adipokines and the translational research potential in small animal patients - Theyse, Lars F. H.; Mazur, Emilia M. (Frontiers in Veterinary Science, 2024)
Osteoartritis (OA) is a debilitating disease affecting both humans and animals. In the early stages, OA is characterized by damage to the extracellular matrix (ECM) and apoptosis and depletion of chondrocytes. OA progression is characterized by hyaline cartilage loss, chondrophyte and osteophyte formation, thickening of the joint capsule and function loss in the later stages. As the regenerative potential of cartilage is very limited and osteoarthritic changes are irreversible, prevention of OA, modulation of existing osteoarthritic joint inflammation, reducing joint pain and supporting joint function are the only options.Progression of OA and pain may necessitate surgical intervention with joint replacement or arthrodesis as end-stage procedures. In human medicine, the role of adipokines in the development and progression of OA has received increasing interest. At present, the known adipokines include leptin, adiponectin, visfatin, resistin, progranulin, chemerin, lipocalin-2, vaspin, omentin-1 and nesfatin. Adipokines have been demonstrated to play a pivotal role in joint homeostasis by modulating anabolic and catabolic balance, autophagy, apoptosis and inflammatory responses.In small animals, in terms of dogs and cats, naturally occurring OA has been clearly demonstrated as a clinical problem. Similar to humans, the etiology of OA is multifactorial and has not been fully elucidated. Humans, dogs and cats share many joint related degenerative diseases leading to OA. In this review, joint homeostasis, OA, adipokines and the most common joint diseases in small animals leading to naturally occurring OA and their relation with adipokines are discussed. The purpose of this review is highlighting the translational potential of OA and adipokines research in small animal patients.